Exploring the Diagnostic Potential of Video-Based Breathing Control Training: A Sonographic Evaluation of Abdominal Organ Measures - Hassan MG; AlOtaibi AM; Altuwaym RH; Alnuwaysir RH; Alharbi RB; Alnajashi LM; Alsaber MK; Aldakan HF; Hawesa HM; Abdelgabar ZA; Aldahes AS; Yaqob MG (International Journal of General Medicine)
Mahasin G Hassan,1 Afnan M AlOtaibi,1 Raghad H Altuwaym,1 Reem H Alnuwaysir,1 Renad B Alharbi,1 Lama M Alnajashi,1 Mayer K Alsaber,1 Hetaf F Aldakan,1 Halima M Hawesa,1 Zohida A Abdelgabar,2 Asma S Aldahes,1 Mohammed G Yaqob3 1Department of Radiological Sciences, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 2Department of Radiological Sciences, Al-Ghad International Colleges for Applied Sciences, Madina, Saudi Arabia; 3Software Development Department, N24 Company Limited, Riyadh, Saudi ArabiaCorrespondence: Mahasin G Hassan, Department of Radiological Sciences, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, PO Box 84428, Riyadh, 11472, Saudi Arabia, Tel +966553661276, Email mghassan@pnu.edu.saBackground: Breathing control training programs have gained attention due to their potential to influence diagnostic procedures. However, the role of video-based tools to demonstrate breathing maneuvers during sonographic quantification of abdominal organs needs to be studied more. This study explores the impact of a video-based breathing training program on sonographic examination of abdominal organs.Methodology: This quasi-experimental study recruited 49 healthy volunteers at the ultrasound lab of College of Health and Rehabilitation Sciences in Princess Nourah bint Abdul Rahman University. The study employed a video-based breathing control training program that includes diaphragmatic breathing exercises. Sonographic assessments of abdominal organs were conducted before and after the intervention period using standardized protocols. Data was analyzed using SPSS V 28.Results: The right renal length (p-value < 0.001), thickness (p-value 0.025), and volume measured (p-value < 0.001) were significantly improved following the video training. Similarly, splenic length (p-value 0.015), width (p-value < 0.001), and volume (p-value 0.001). Additionally, the operator time demonstrated a notable decrease from 13.14 ± 3.4 to 8.1 ± 3.5 minutes after the video training intervention (p-value < 0.001).Conclusion: The study provides evidence for the beneficial effects of a video-based breathing control training program on sonographic quantification of abdominal organs. These findings suggest potential clinical utility for integrating video-based breathing interventions into practice, although study limitations require further validation and generalization. Nonetheless, the study highlights the promising role of breathing control training in enhancing the diagnostic accuracy of abdominal sonography.Keywords: breathing, training, kidney, spleen, sonography